MENINGKATKAN HASIL BELAJAR DENGAN MENGGUNAKAN PENERAPAN METODE KOOPERATIF SCRIPT SISWA KELAS IV SD NEGERI 167647 TEBING TINGGI - Benny Hutapea (PGSD Universitas Negeri Medan, 2018)
This study aims to improve student learning outcomes using the application of the cooperative method script fourth grade students of SD Negeri 167647 Tebing Tinggi City. The cooperative script method is one of several methods in the cooperative learning model (Cooperative Learning). This method was proposed by Danserau and friends in 1985. Cooperative learning is a group learning activity to work together to help construct concepts, solve problems or inquiry (Suyatno, 2009: 51). From the results of the learning activities that have been carried out it can be concluded that the application of cooperative script learning methods has a positive impact in increasing students' interest and learning achievement on Indonesian language subjects in Class IV 167677 SD Negeri Tebing Tinggi which is characterized by an increase in student learning completeness in each cycle. The application of the Cooperative Script method makes students more active, accountable for their assignments and delivers news / story ideas about Indonesian language learning material taught by teachers individually or in groups.Keywords: Learning Outcomes, Cooperative Scripts, Indonesian Language